A method of purifying alpha-synuclein in E. coli without chromatography. Issue 1 (January 2021) - Kamboj, Sumaer; Harms, Chase; Kumar, Lokender; Creamer, Daniel; West, Colista; Klein-Seetharaman, Judith; Sarkar, Susanta K.
Abstract: Research has implicated alpha-synuclein (aSyn) in pathological protein aggregation observed in almost all patients with Parkinson's disease and more than 50% of patients with Alzheimer's disease. An easy and inexpensive method of purifying aSyn and developing an in vitro model system of Lewy body formation would enhance basic biomedical research. We report aSyn purification technique that leverages the amyloidogenic property of aSyn suitable for purifying monomeric aSyn without chromatography and denaturing agents. We expressed full-length and untagged aSyn in Rosetta(DE3) pLysS and purified 60 μg of aSyn from 500 mL culture within 24 h. After IPTG-induced expression of aSyn in E. coli, we disrupted the cells with a sonicator. We centrifuged the cell lysate in a 15 mL tube, which leads to aSyn-induced aggregation of native E. coli proteins. After removing aggregates, centrifugation in a 30 kDa cut-off filter followed by a 10 kDa cut-off filter led to purified water-soluble aSyn. The identity of aSyn was confirmed by Western blot using anti-aSyn antibody and Edman sequencing. Its mass was determined to be 14.6 kDa using a MALDI TOF-MS mass spectrometer. The majority of aSyn led to water-suspended (as opposed to precipitated) aggregation of E. coli proteins with visible fibrous structures. The broad-spectrum binding and amyloidogenic property of aSyn is thus not only useful for inexpensive aSyn production for diverse applications, but it also expands studying its possible roles in human physiology. The aggregate of E. coli proteins induced by aSyn during the purification process may serve as a Lewy body model. Abstract : Recombinant human alpha-synuclein, aggregation induced by alpha-synuclein, Lewy body model system, Western blot.